Stylistic synthesis in the twentieth century: a modern compositional approach in the music of Samuel Barber - Bell, Andrew (Kansas State University, 2023)
Samuel Barber was a prominent figure in American twentieth-century concert music, recognized for composing some of the period’s most performed chamber, orchestral, and vocal works. As a result of his popularity, Barber benefited from a continual demand for commissions, performances, and recordings of his works, a luxury that quite few of his contemporaries enjoyed. Even so, criticisms of Barber’s compositional approach were not uncommon, and his music was at times regarded as overly conservative and out of touch with modern developments in compositional technique. Possibly as an outcome of this, only limited scholarly research on Barber’s music and compositional style has been published. In recent decades, a renewed interest in Barber’s work has begun to contribute to a growing body of research on his technique, yet more work is to be done to contextualize his position in the framework of twentieth century concert music. The purpose of this report is to discuss concise examples in Barber’s oeuvre where the lyrical qualities of his music intersect with modern practice, as a means of better understanding his approach to solving twentieth century compositional problems. In a period where experimentation was highly propagated, Barber managed to strike a balance between individual expression and technical development, contributing works of intellectual interest to the repertoire that maintain a strong emotional pull. In the music analyzed in this report, particularly, Barber demonstrates an exceptional ability to synthesize the developments of the period with a well-defined individual voice. The young composer can benefit from Barber’s example by always striving to merge learned technique with individual style.
Keywords: Samuel Barber; Ballade Opus 46; Nocturne Opus 33; Stylistic synthesis in music composition; Serialization of pitch; Twentieth century compositional technique